PENGARUH PENDAPATAN PETANI KARET TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA SEMUNTAI KECAMATAN SEPAUK KABUPATEN SINTANG - Nina Pujiarti; Nuraini Asriati; Husni Syahrudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to determine the effect of rubber farmers' income on the welfare of the community in Semuntai Village, Sepauk District, Sintang Regency. The type of research approach used is quantitative research with survey methods in the form of relationship studies/correlation studies. The data sources of this research are rubber farmers in Semuntai Village with a sample of 106 respondents. Data collection techniques used in this research are indirect communication techniques and documentary study techniques. Data collection tools used in this study were questionnaires and documentation. The research instrument is validity test and reliability test. The results showed (1) the average income of rubber farmers was included in the medium income group with the average income received by rubber farmers in one month of IDR 1,500,000 – IDR 2,500,000 and included in the good category with a percentage of 81.06%. (2) community welfare is included in the good category with a percentage of 80.77% in terms of children's education, health, housing, information and communication technology. (3) the income of rubber farmers has a significant effect on the welfare of the community by 89.5% while 10.5% is influenced by other variables or factors that are not investigated further.Keywords: Rubber Farmer Income, Community Welfare